Findlay & Co’s Illustrated Catalogue 1874-75 - Cottrell, William (Architectural History Aotearoa, 2018)
Dunedin mill owner George Findlay published New Zealand’s first cottage plans for sale to the public in March 1874. His extensive steam-powered factory bounded by Cumberland, Castle and Stuart Streets supplied all requisites for "cottages, doors, sashes, mouldings, architraves and every description of furnishings for building purposes." The only surviving copy has 30 pages of elevations and floor plans for seven cottages of three to seven rooms. At 1/8 inch to the foot, according to the Otago Witness (9 May 1874) they were "prepared so as to be fit to be put into a builder’s hands" and "contain[ed] not fancy sketches but drawings which are practical and to scale." It was boom time in Dunedin, the wealthiest city in the colony, with immigrant demands for housing and for furnishing. Renegade printer Samuel Lister produced another catalogue in July 1875 but this time for George Street cabinetmakers Craig and Gillies, yet both catalogues shared some designs in common. This paper examines what prompted New Zealand’s first completely illustrated architectural plans, woodware and furnishing publications to be made, what they contained and most interestingly how they were made.